Simple Bone Cyst in Spinous Process of the C4 Vertebra - Coskun, Bilgen; Akpek, Sergin; Dogulu, Fikret; Uluoglu, Ömer; Eken, Gülçin (American Journal of Neuroradiology, 2004)
Summary: Simple bone cysts are common, benign, fluid-filled, cystic lesions that occur mostly in the metaphysis of the long bones and are rarely found in vertebrae. A case of a simple bone cyst in the spinous process of the fourth cervical vertebra in a 26-year-old woman is reported. According to the radiologic findings, the lesion was identified as a simple bone cyst, and the diagnosis was verified by surgical and histopathologic examinations.